Adaptive Step Size Based Hill-Climb Search Algorithm for MPPT Control of DFIG-WECS With Reduced Power Fluctuation and Improved Tracking Performance - Uddin M.N.; Amin I.K. (Taylor and Francis Inc., 2023)
Controllers; Electric fault currents; Electric machine control; Electric power generation; Energy conversion; Maximum power point trackers; Speed; Turbines; Wind; Wind power; Adaptive step size; Doubly fed induction generator (DFIG); hill climb search; Maximum Power Point Tracking; Weighted average method; Asynchronous generators